IMPROVING STUDENTS’ WRITING SKILLS BY USING THE AUDIO-LINGUAL METHOD IN THE SIXTH SEMESTER OF THE ENGLISH DEPARTMENT AT HKBP NOMMENSEN MEDAN - Aslina Laia, Jernih; Nasution, Nelinda Kristauli; Simarmata , Rina Oktavia; Marbun, Paulina; Hasugian, Nova Kalsim; Juwita, Veni (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to improve students' writing skills by using the Audio-Lingual Method on Semester Six students of the English Department of HKBP Nommensen University Medan. The main problem identified was the students' low writing ability, characterized by incorrect grammar, limited vocabulary, and poor sentence structure. To overcome these problems, this study used the Audio-Lingual Method approach which emphasizes repetition and intensive practice in listening before writing. This research uses the Classroom Action Research method by conducting tests to see the improvement of students' skills. The data collection technique in this research is by collecting results from Observation, Interview, Questionnaire, Documentation, Test and Evaluation, Statistical Analysis, and data analysis techniques conducting Observation, Interview, Documentation, Test, and Statistical Analysis. The results showed a significant improvement in students' writing skills after the application of the Audio-Lingual Method. Students showed improvement in the use of correct grammar, richer vocabulary, and better sentence structure. Audio Lingual is effective in improving student's writing skills and can be adopted as one of the methods of teaching writing in higher education.